On Cellular Networks Supporting Healthcare Remote Monitoring in IoT Scenarios - Petroni, Andrea; Salvo, Pierpaolo; Cuomo, Francesca (Frontiers in Communications and Networks, 2021)
In the next few years, fundamental technological transitions are expected both for the wireless communications, that will be soon resulting in the 5G Era, and for the kind of pervasiveness that will be achieved thanks to the Internet of Things. The implementation of such new communication paradigms is expected to significantly revolutionize people's life, industry, commerce and many daily activities. Healthcare applications are addressed to be in the set of the most impacted ones. Sadly related to the COVID-19 pandemic currently afflicting our society, health remote monitoring is becoming a fundamental and urgent application. Indeed, the overcrowding of hospitals and medical facilities has unavoidably created delays and key issues for what concerns medical assistance. In several cases, asymptomatic or light symptomatic COVID-19 patients have to be continuously monitored to prevent emergencies, and such an activity does not necessarily request hospitalization. In this direction, this paper investigates the potentiality of cloud-based cellular networks to support remote healthcare monitoring applications implemented in accordance to the IoT paradigm combined with future cellular systems. The idea is to conveniently replace the physical interaction between patients and doctors with a reliable virtual one, so that hospital services can be reserved for emergencies. Specifically, we investigate the feasibility and effectiveness of remote healthcare monitoring by evaluating its impact on the network performance. Furthermore, we discuss the potentiality of medical data compression and how it can be exploited to reduce the traffic load.